Original researchEvaluation of the level of antibodies against Chlamydophila (Chlamydia) pneumoniae in post-surgery heart ischaemia patients and their clinical conditions – a six-year study - Brykczyński, Mirosław; Żych, Andrzej; Gorący, Iwona; Mączyńska, Iwona; Wojciechowska-Koszko, Iwona; Mokrzycki, Krzysztof; Giedrys-Kalemba, Stefania; Sielicki, Piotr (Archives of Medical Science, 2010)
Introduction: Inflammatory conditions modulated by Chlamydophila (Chlamydia) pneumoniae are considered to play an important role in the onset of atherosclerosis. In this paper we present the results of progressive observation of C. pneumoniae antibody titres in patients who underwent coronary artery bypass graft (CABG). Material and methods: The objective of our research was a prospective observation of antibody titres in IgA and IgG class antibodies against C. pneumoniae using indirect immunofluorescence in a group of 155 post-surgery CABG patients suffering from heart ischaemia. The microbiological test results were compared with patients’ present coronary complaints evaluated on the CCS scale during a six-year period. Results: Six years after CABG, 128 patients (82.6%) are still alive. During the study a positive serological conversion of antibody titres was observed in 36 patients in the IgA class antibodies, and in 26 patients in the IgG class. The group of patients with no antibodies against C. pneumoniae decreased from 23.2 to 3.4%, while the group of patients with antibodies in both IgG and IgA classes increased from 52.3 to 83.9%. The average CCS degree decreased from 3.18 before CABG to 1.65 in the present study. Conclusions: These results show no connection between the serological symptoms of chronic C. pneumoniae infection and coronary complaints evaluated on the CCS scale during a six-year study on post-CABG patients suffering from heart ischaemia. The surgical treatment of heart ischaemia brought about long-term improvement in the coronary condition of the observed group of patients.